GReening the city: criteria and indicators for evaluating the effectiveness of small urban parks in promoting urban resilience to climate change - Mohammad Sabri, Siti Afiqah; Ponrahono, Zakiah (Malaysian Institute Of Planners, 2024)
As cities face the challenges of climate change, small urban parks offer a promising solution for promoting urban resilience. These parks can mitigate the impacts of climate change by providing carbon sequestration, reducing the urban heat island effect, and improving storm water management. They can also serve as a key adaptation strategy by providing shade and cooling, reducing air pollution, and enhancing social cohesion and community engagement. However, there is a need for criteria and indicators that can guide the design, implementation, and management of small urban parks for climate change mitigation and adaptation. This paper proposes a set of criteria and indicators that can be used to evaluate the effectiveness of small urban parks in promoting urban resilience. The criteria include ecological, social, economic, governance dimensions, and the indicators are measurable, relevant, and practical. The proposed framework can support decision-making processes for planners, policymakers, and practitioners to prioritise and allocate resources for small urban parks that can contribute to climate change mitigation and adaptation in cities.